AUDIT PROCEDURES FOR EVALUATION OF MANAGEMENT STAFF'S STATEMENTS ON INTANGIBLE ASSETS - SHERSTIUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article describes the aspects of evaluating the statements of management regarding the information of intangible assets and transactions with them in the financial statements. As a result of study, it is substantiated that the feature of intangible assets in the context of their accounting and auditing is the lack of tangible form. This circumstance determines the content of the procedures to be used for the intangible assets audit.It is established that during the audit the data of reporting forms are examined as a set of statements that characterize the balances on the accounts at the reporting date, the content and results of business transactions with intangible assets during the reporting period, as well as data in financial reporting forms. Account balances are characterized by statements of management regarding the existence of intangible assets, ownership of rights to them, completeness of reflection and evaluation of relevant objects. Intangible assets transactions are disclosed through the statements of origin, completeness, accuracy of valuation and correspondence of accounts and closing of the period. The basis for the presentation of information about intangible assets in the financial statements are the statements of classification, presentation and disclosure.In order to obtain and evaluate audit evidence on relevant data, it is proposed to use audit procedures such as inspection, observation, request and confirmation, recalculation, re-execution and analytical procedures. However, each statement can be verified by applying more than one procedure. This will help increase the level of reliability of audit evidence and the validity of assurance in the audit results.The results of the study will help to improve the audit methodology of intangible assets of economic entities.
Keywords: audit; audit procedures; intangible assets; statements of management staff; audit evidence